The Students’ Perception on English Learning Media During Covid-19 Pandemic - Andi Nindyia Nur Ramadani Putri; Kisman Salija; Maemuna Muhayyang (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study aims to determine students' perceptions of English learning media used by their teachers during the covid-19 pandemic. The researchers applied descriptive qualitative method to achieve the research objectives. The data collected were in the form of questionnaires and interviews. The subjects of this study were students of SMPN 1 Tarowang. The population used in this study is class VIII consisting of four classes and using 5 samples for each class using random sampling where the total sample is 20 students. Based on the findings and discussion of the previous chapter, the researchers conclude the Students' perceptions of the use of WhatsApp group media in online English learning at SMPN 1 Tarowang have many positive perceptions. This is supported by questionnaires and interviews which show that many students have positive perceptions in their responses. Of the several themes found, two of them are included in positive perceptions, namely flexibility and affective. Perception of using WhatsApp group media explained that WhatsApp group was an easily accessible medium and almost all students already understood its use. Meanwhile, according to students, zoom meetings have features that are not so easy to understand. WhatsApp media and zoom meetings should be used in schools that have easy internet access or in schools located close to the city.